2012
DOI: 10.1177/000494411205600107
|View full text |Cite
|
Sign up to set email alerts
|

Moral Development and Student Motivation in Moral Education: A Singapore Study

Abstract: Recent world events such as the threat of terrorism and the global economic crises have rekindled an interest in ethics and values education. This study, conducted in Singapore, combines a Kohlbergian approach to the assessment of moral judgement with a framework based on the self-determination theory to assess the motivational regulations of adolescent students towards civics and moral education (CME). The findings show that the Singaporean students' development of moral reasoning follows the trend prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
0
8
0
14
Order By: Relevance
“…Their service communicated the best example of caring and altruistic giving, much akin to an extended family, and it was described by the RJ students in the study. It is similar to a communiqué of moral teaching by various role models through the functions of singing, signing, and catering, resonating in Koh's (2012) review of informal approaches to value education, as claimed by Sharma and Mohite (2007). Differing from the competitive sense of learning for grades in an ordinary classroom, the BSA experience was effectively associated with a harmonious environment in which good is the only choice and the end.…”
Section: Moral Models For Caringmentioning
confidence: 70%
See 1 more Smart Citation
“…Their service communicated the best example of caring and altruistic giving, much akin to an extended family, and it was described by the RJ students in the study. It is similar to a communiqué of moral teaching by various role models through the functions of singing, signing, and catering, resonating in Koh's (2012) review of informal approaches to value education, as claimed by Sharma and Mohite (2007). Differing from the competitive sense of learning for grades in an ordinary classroom, the BSA experience was effectively associated with a harmonious environment in which good is the only choice and the end.…”
Section: Moral Models For Caringmentioning
confidence: 70%
“…Her Singapore study, which she conducted to assess the motivational regulations of adolescent students toward civics and moral education (CME), found the student participants showed a moderate degree of self-determined motivation in CME, but a high correlation between identified regulation and intrinsic motivation suggested opportunities for choice and ownership of their moral learning. Citing Berkowitz and Bier's (2007) finding, Koh (2012) concluded that an effective CME attempts to be engaging and relevant to students to include professional development, interactive pedagogical strategies, explicit focus on ethics or character, social and emotional competencies training, behavioral management strategies, elements of community service, and service learning (p. 96).…”
Section: Moral Educationmentioning
confidence: 99%
“…There are 3 levels, and each level there are 2 stages. These stages of moral development apply universally and in a certain order [6]. Table 1 shows the six stages of moral reasoning presented by Kohlberg (1975).…”
Section: Introductionmentioning
confidence: 99%
“…Caroline Koh, mentions that there are problems in moral education, which is proven that there are criminal acts in adolescents in modern society, both in school and outside of school [4]. These conditions are due to increased adolescent moral emotions, which also show the development of morality in adolescence [1] .…”
Section: Introductionmentioning
confidence: 99%